Technical explorations for manufacturing of NiTi unibody vascular stents through metal injection molding: Materials performance, fatigue properties and biocompatibility - Dongyang Li; Junwei Wang; Changhai Du; Hao He; Zheyu He; Tun Wang; Chang Shu; Yimin Li; Jing Pan (Materials & Design)
Compared with the conventional laser cutting and braided method, this research aimed to produce unibody NiTi vascular stents by metal injection molding (MIM), simplifying the manufacturing process. MIM NiTi alloys and stents with a low oxygen content of 0.17 % were obtained via strict oxygen control. Sintered Ni4Ti3 precipitates can be observed in both micron and nanometer scales. The MIM NiTi alloy has a tensile strength of 812 MPa, an elongation of 5.7 %, and full recovery at 5 % pre-strain. During 3.96 × 108 cycle-simulated in vitro fatigue tests, the MIM NiTi stents essentially maintained a constant diameter without any marked damage, although local pitting was observed. The biocompatibility of MIM NiTi was evaluated based on toxicity, migration, and adhesion of the human umbilical vein endothelial cells. The hemolysis rate was as low as 0.4 %. This study provides a new manufacturing strategy for NiTi self-expanding vascular stents. Additionally, it aimed to develop porous and gradient porous NiTi vascular stents using the characteristics of MIM process.